Analysis of Leading Sectors and Structural Shifts in the Economy in Tojo Una-Una District in 2019-2023 - Rezaldi, Rezaldi; Yunus, Santi; Sading, Yunus; Yunus, Rita; Musdayati, Musdayati (Transpublika Publisher, 2025)
This study aims to analyse the leading sectors and shifts in economic structure in Tojo Una-Una Regency between 2019 and 2023, using the Location Quotient (LQ) and Shift-Share Analysis methods. The main objective of the research is to identify sectors that play an important role in regional economic growth and evaluate the factors that affect the performance of these sectors. The data used includes the Gross Regional Domestic Product (GRDP) of Tojo Una-Una Regency and Central Sulawesi Province during the period. The results of the analysis show that the agriculture, forestry and fisheries sector and the services sector such as education, health and accommodation provision have a major contribution to the regional economy. The Real Estate sector was recorded as the sector with the highest LQ, indicating enormous growth potential. In contrast, the manufacturing and mining sectors experienced a significant decline in competitiveness. Shift-Share analysis shows that most of the growth of the leading sectors is influenced by local factors, with the agricultural sector being the main contributor in the shift of the regional economy. This study recommends infrastructure development, labour quality improvement, as well as policies that support non-base sectors to improve the competitiveness and diversification of the regional economy.